Akalisie Novalinga performing in the Native Peoples Area - Marcia Colthorpe
Caption on verso reads: "Akalisie Novalinga. 100% P.28. Photo property of Mariposa Folk Festival. Please credit Marcia Colthorpe." Digitization possible through funding from Young Canada Works grant for the summer of 2018. We acknowledge the financial support of the Government of Canada. Nous reconnaissons l'appui financier du gouvernement du Canada.